2015
DOI: 10.13152/ijrvet.2.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Qualification of Adult Educators in Europe: Insights From the Portuguese Case

Abstract: This article explores the role of the European Union in defining an adult education policy and the way European countries appropriate those guidelines and implement them in their realities. These policies have been widening and diversifying adult education, creating the necessity of qualifying educational professionals. With the implementation of some adult education political measures, new educational practices were developed and new professional activities were born. This investigation is about the qualifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 9 publications
0
14
0
8
Order By: Relevance
“…For example, the extensive ALPINE study (Research voor Beleid & PLATO, 2008) has revealed that the field of adult learning and education has been characterized by its fragmented trainings for its ALFs' professional development. This finding has been also confirmed by countryspecific studies within Europe, for example in Denmark and Sweden (Andersson et al, 2012;Milana & Larson, 2010) (Paulos, 2015), Bulgaria, Cyprus, Greece, and Turkey (Zarifis, 2009). Przybylska (2008) describes several common pathways (e.g.…”
Section: Adult Learning Facilitators' Professional Developmentmentioning
confidence: 65%
See 1 more Smart Citation
“…For example, the extensive ALPINE study (Research voor Beleid & PLATO, 2008) has revealed that the field of adult learning and education has been characterized by its fragmented trainings for its ALFs' professional development. This finding has been also confirmed by countryspecific studies within Europe, for example in Denmark and Sweden (Andersson et al, 2012;Milana & Larson, 2010) (Paulos, 2015), Bulgaria, Cyprus, Greece, and Turkey (Zarifis, 2009). Przybylska (2008) describes several common pathways (e.g.…”
Section: Adult Learning Facilitators' Professional Developmentmentioning
confidence: 65%
“…However, participation in these programmes is strongly dependent on individual decision (Buiskool et al., 2009; Milana & Larson, 2010; Przybylska, 2008; Research voor Beleid & PLATO, 2008); consequently, professional development of ALFs has been treated as an individual responsibility even though there should have been regulatory frameworks (Milana & Larson, 2010). This, indeed, has created the common situation that many ALFs enter into the field without any specialization in adult learning and teaching in numerous European countries (Čepić & Mašić, 2016; Gedvilienė et al., 2018; Kušić et al., 2015; Paulos, 2015; Research voor Beleid & PLATO, 2008).…”
Section: Adult Learning Facilitators’ Professional Developmentmentioning
confidence: 99%
“…He found that unified recognition processes were unlikely due to the unmanageable heterogeneity of professional roles and competences to be recognized. Paulos (2015) focused on the EU's contribution to the definition of adult education policy at a country level. Using the example of education policy structures in Portugal, the author explained that the professionalization of adult educators in Portugal was in a process of alignment.…”
Section: European Vet Policy and Cross-country Comparisons In The Eumentioning
confidence: 99%
“…What are the implications of the instability of work contexts on their professional identity? It is important to note that the instability of working conditions experienced by adult educators can lead them to a process of disinvestment both in terms of attending continuing education programmes and in terms of the involvement with their professional activity (Paulos, 2015). Reflecting on these questions and a subsequent attempt to respond them may contribute to having adult educators better prepared to work in times characterised by instability and uncertainty.…”
Section: Final Remarksmentioning
confidence: 99%